Ireland Country Report: Eufori Study. European Foundations for Research and Innovation - Cannon, Sheila; Donnelly Cox, Gemma (European Commission, 2015)
Through the application of the EUFORI analytical framework to R&I foundations in Ireland, we have established that the field of foundation philanthropy is small, and foundation funding for research and innovation comprises a very small part of it. On one level, this is no surprise. Donoghue’s review of the total population of foundations in Ireland (2004, 2007) concluded that there are very few Irish grantmaking or operating foundations. Anheier and Daly (2007) classify Ireland as a statist peripheral welfare regime (Anheier and Daly, 2007) – one in which the importance of foundations is low, and the ones that do exist tend to function as service providers that compensate for the shortcomings of the State. However, on another level the relative absence of R&I foundations is quite puzzling. Ireland has a large nonprofit sector and an economy that is highly dependent on investment in research and innovation. As the second and third citations quotations on the previous page illustrate, in the current period of economic austerity in which the State continues to cut its investment in STI, there appears to be a clear rationale for increased levels of private investment in research and innovation.In this report on R&I foundations in Ireland, we start by reviewing research on foundations in Ireland in general. An analysis, largely conducted by one scholar (Donoghue, 1998, 2004, 2007), has provided a picture of a small sector with many features particular to Ireland. From the mid-2000s, on the back of an economic boom and increased public sector support for the promotion of private philanthropy, there was some discussion of philanthropy in the popular press and some initial promotion of foundations as philanthropic vehicles (see for example Gaffney, 2008; Molloy 2008; Wilhelm 2008). From mid-2008 onwards, there have been cross-cutting influences affecting the field. The most dramatic of these is the knowledge that the largest grantmaking foundation in the country, the Atlantic Philanthropies, will cease operations in Ireland by the end of 2016. Whilst Atlantic is not an R&I foundation, it has played a critical role, particularly in the period 1998-2010, as a foundation that supports R&I. Atlantic has operated in Ireland for nearly two decades and as will be detailed in this report, has jolted the philanthropic landscape through its own and its joint programs of grantgiving, and through its support for the development of a philanthropic infrastructure. Other factors include the very difficult financial conditions that have contributed to a challenging resource environment for philanthropy (Healy and Donnelly-Cox, 2016 forthcoming). There have also been a number of institutional developments which ultimately should facilitate philanthropy. The 2009 publication of the Charities Act has strengthened the institutional con-text in which philanthropy operates. Not least of its provisions is a much clearer regulatory framework. Collaboration between philanthropy and the State has been manifest in the operation of the Forum on Philanthropy, a cross-sector body that is currently leading the National Giving Campaign with the aim of growing planned giving within the country by 10 % per year.
PUBLISHED
Brussels, Belgium
Keywords: Foundation landscape; R&I foundations; Nonprofit sector; Corporate/Nonprofit Philanthropy; FOUNDATIONS; INNOVATION; Research Foundations